2018
DOI: 10.1097/md.0000000000012244
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health and colorectal adenoma in a screening population

Abstract: Although periodontal disease and gastrointestinal tract health are closely associated, few studies have investigated whether periodontitis is a risk factor for colorectal adenoma. The aim of this study was to investigate whether there is an association between periodontitis and the risk of colorectal adenoma in asymptomatic healthy people.From January 2013 to October 2015, we retrospectively enrolled 42,871 patients who underwent health screening at Kangbuk Samsung Hospital in South Korea. Demographic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
1
21
1
3
Order By: Relevance
“…As stated above, multiple epidemiological studies showed a strong association between orodigestive cancers and poor oral health [97102], periodontal diseases [103106], tooth loss [98, 99, 101, 102, 106, 107], and periodontal diagnostic parameters such as clinical attachment loss (CAL) and alveolar bone loss [108, 109]. Additionally, patients showing gastric precancerous lesions were more likely to have higher percentages of sites with gingival bleeding [97, 110].…”
Section: Association Between Periodontitis and Orodigestive Cancermentioning
confidence: 99%
“…As stated above, multiple epidemiological studies showed a strong association between orodigestive cancers and poor oral health [97102], periodontal diseases [103106], tooth loss [98, 99, 101, 102, 106, 107], and periodontal diagnostic parameters such as clinical attachment loss (CAL) and alveolar bone loss [108, 109]. Additionally, patients showing gastric precancerous lesions were more likely to have higher percentages of sites with gingival bleeding [97, 110].…”
Section: Association Between Periodontitis and Orodigestive Cancermentioning
confidence: 99%
“…A body of evidence has shown that cytokines produced in inflamed periodontal tissues, together with virulence factors from periodontal pathogens and oral microbial agents, may gain access to the circulation, and, consequently, induce systemic inflammation [ 5 , 43 ]. Accordingly, it has been proposed that non-resolving periodontal inflammation may affect systemic inflammatory diseases and that cytokines may be considered as a possible pathogenic link between periodontitis and various systemic diseases, including IBD and CRC [ 4 , 5 , 6 , 7 , 38 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following key words, achieved by studies investigating either colorectal cancer or periodontitis or both of them [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], were employed in the literature search and were logically combined with the Boolean operators AND, OR, NOT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that periodontitis defined by a self-report of oral health increases the risk of colorectal adenoma 38 . However, no study has ever investigated an association of proximal CRNs and periodontitis defined by objective criteria.…”
Section: Introductionmentioning
confidence: 99%